2017
DOI: 10.4236/cweee.2017.61006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reference Conveyance Parameter Usage on Real Time Canal Performance: The Case of Fentale Irrigation Scheme in Ethiopia

Abstract: In designing a canal system, a major problem is to decide what conveyance parameter to apply in the calculations. Since basic knowledge on this subject is lacking, it is usually taken from literatures. Most of the irrigation projects in Ethiopia are found to work below their expectation. One of the main reasons is the conveyance parameters variation from the expected (design) value which ultimately affects the envisioned conveyance efficiency. To evaluate this variation, Fentale irrigation scheme was used as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In any case, there is an orifice offtake, pump station, and checkpoint at the end of every pool. This example starts from an initial steady state, where the upstream boundary condition is a flow rate through gate one of 10 m 3 /s, and the checkpoint condition (at the end of each pool) is a water level of 2.0 m, which involves a constant flow rate (scheduled demand) of 5 m 3 /s by the orifice offtake regarding the initial canal conditions (Manning's coefficient [26,27], gate position, etc.). Furthermore, the water level is measured at every checkpoint every 5 min during an operational horizon of 4 h.…”
Section: Practical Example: a Canal With Two Poolsmentioning
confidence: 99%
“…In any case, there is an orifice offtake, pump station, and checkpoint at the end of every pool. This example starts from an initial steady state, where the upstream boundary condition is a flow rate through gate one of 10 m 3 /s, and the checkpoint condition (at the end of each pool) is a water level of 2.0 m, which involves a constant flow rate (scheduled demand) of 5 m 3 /s by the orifice offtake regarding the initial canal conditions (Manning's coefficient [26,27], gate position, etc.). Furthermore, the water level is measured at every checkpoint every 5 min during an operational horizon of 4 h.…”
Section: Practical Example: a Canal With Two Poolsmentioning
confidence: 99%
“…This difference is due to the conveyance loss, which caused by the breaking of the canals, siltation and improper cleaning of the grasses in the canals. Similarly Mohammed [3] reported that, the difference between the existing conveyance efficiency and expectation (design) was due to improper operation and maintenance of the canals.…”
Section: Overall Canals Conveyance Efficiency Performancementioning
confidence: 99%
“…It is the proportion of the outflow rate to the inflow rate of a system [2]. Water delivered to the farm or sphere is usually less than the water diverted from the root due to loss [3,13]. The conveyance efficiency mainly depends on the length of the canals, the soil type or the permeability of the canal banks and the condition of the canals [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seepage loss in the irrigation canals accounts for the major portion of water conveyance loss (98.37%) while approximately 0.3 percent of the total stream is lost due to evaporation [1]. The damage to the canal hydraulic parameters triggers to seepage losses, therefore, the assessment of the potential cause of canal hydraulic inefficiency is vital for the sustainable functionality of irrigation schemes [6]. Aquatic weeds may be defined as upsetting or unsightly plants growing where they are not wanted.…”
Section: Introductionmentioning
confidence: 99%